Workforce Skills and Innovation An Overview of Major Themes in the Literature - Toner, Phillip (OECD Science, Technology and Industry Working Papers, 2011)
This paper provides an account of the main approaches, debates and evidence in the literature on the role of workforce skills in the innovation process in developed economies. It draws on multiple sources including the innovation studies discipline, neoclassical Human Capital theory, institutionalist labour market studies and the work organisation discipline. Extensive use is also made of official survey data to describe and quantify the diversity of skills and occupations involved in specific types of innovation activities